A Review of Reforming Processes in the Railway Manufacturing Industry : Case Study of PT. Industri Kereta Api (Persero) - Kristanta, Stephanus Yosi; Setyani, Atik; Sudaryanto, Sudaryanto; Syukron, Muhammad; Santoso, Muji (Journal of Metallurgical Engineering and Processing Technology, 2024)
The railway manufacturing industry is critical for developing efficient and sustainable mass transportation systems. PT. Industri Kereta Api (Persero) (PT. INKA), a leading company in Indonesia, faces significant challenges due to deformation caused by residual stress during welding processes. This study reviews various reforming techniques implemented by PT. INKA to address these issues. The objectives include evaluating the effectiveness of these techniques and identifying potential improvements. Methods such as post-weld heat treatment (PWHT), controlled cooling, and mechanical tools are analyzed for their ability to mitigate deformation. The study demonstrates that PWHT reduces residual stress and improves material quality by homogenizing the microstructure. Controlled cooling techniques effectively reduce distortion by allowing even temperature distribution during the cooling process. Mechanical tools provide nonthermal methods to stabilize and control deformation, significantly reducing distortion levels. Despite the success of these techniques, PT. INKA faces challenges related to process control and skill variance among workers. The study concludes that while reforming techniques significantly enhance the structural integrity and performance of railway components, consistent implementation and clear guidelines are essential for future improvements. Developing new technologies, enhancing workforce training, and creating comprehensive process guidelines are recommended to maintain high standards and competitiveness in the global market.